Ghana : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This Selected Issues paper on Ghana shows that as a small, open low-income economy, the country faces several major challenges in its conduct of disinflation policy. Ghana has historically experienced volatile and often high inflation rates. The paper also presents a model that recognizes difficulties being faced by Ghana, among them less-than-perfect credibility of announcements of inflation reduction and policymaker aversion both to movements of output from its potential level and to variability in the interest rate.